BUDAYA RESISTENS SISWA TERHADAP PENDISIPLINAN SISTEM SEKOLAH AGAMA (Studi Kasus Madrasah Aliyah Negeri (MAN) Unggulan Palembang) - Muhammad Isnaini (Ta'dib: Jurnal Pendidikan Islam, 2011)
Obedience and compliance of students toward various rules and regulations which are implemented and designed to regulate the behavior of students are called Madrasah discipline, which aims to nurture students' behavior in order not to deviate from those rules and regulations. Besides, Madrasah discipline also aims  to encourage students to behave according to norms, rules and regulations. Behavior of students are formed and influenced by various factors, such as environmental factors, family and Madrasah. Effective supervision toward  the implementation of the educational unit of MAN 2 Palembang will be able to ensure that educational programs implemented in Madrasah can achieve the desired goals. In order to support the learning process, the teacher must have and implement specific strategies so that students can learn effectively. Therefore, an optimal schedule can be obtained and accepted by the students. The condition where students feel tired, sleepy, and  hungry, can cause bored feeling, no concentration and can arise frustration. Consequently, the students often show bad tendency. Resistance is then understood as a response to an initiative change, that is a response of the conversations that shape the reality in which individuals are humans. Conditioning the students to learn actively so that the potential itself (cognitive, affective, and conative) can develop maximally. In addition, it will be trained and the competence will be  formed that is student's competence to do something positively which will eventually form a life skill as a life stock and livelihood.